Sediment cascades: an integrated approach - Burt, Timothy páginas; Allison, Robert
Sediment Cascades: An Integrated Approach provides a comprehensive overview that addresses the transport of sediment through the landscape. Suitable for academic researchers, industry practitioners, research students and advanced level undergraduates, seeking detailed knowledge and an up-to-date review of the recent research literature. The emphasis is on contemporary sediment system dynamics with relevance both to landscape management and landform development. Sediment Cascades: An Integrated Approach begins with an explanation of the need for an integrated approach to sediment delivery systems and introduces the main themes of sediment production, delivery, storage and transfer. Further chapters then focus on specific environments from mountains, through floodplains, to estuaries and the continental shelf. Focuses on contemporary sediment system dynamics and current research Covers a sequence of environments from steep mountains to the continental shelf Highlights the continuity of the subject by linking each component area with its adjacent elements.